Double-stage activation preparation method of high-specific-capacitance supercapacitor carbon-based material
Through the two-stage activation preparation method, peanut straw is subjected to two-stage chemical activation and pickling treatment, which solves the problem of difficult to prepare high-specific capacitance carbon-based materials in the prior art, and achieves the goal of excellent electrochemical performance and environmental protection and economicality.
Patent Information
- Application Number
- CN202411598242.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
It is difficult to prepare high-specific capacitance carbon-based materials that meet the performance requirements of supercapacitor electrode materials through single-step chemical activation or physical-chemical dual-stage activation, especially peanut straw with higher nitrogen content as the material.
By adopting the two-stage activation preparation method, the peanut straw is washed, dried, crushed and sieved, and mixed with the activator for two-stage chemical activation. The first stage is activated at 350-400°C for 60-90 minutes, and the second stage is Activation at 700°C for 10 to 15 minutes, followed by pickling and drying, and finally a carbon-based material with a high specific capacitance was obtained.
The peanut straw-based carbon-based material prepared by this method has better electrochemical performance than existing activated carbon for supercapacitors, meets the performance requirements of supercapacitor electrode materials, and uses agricultural waste to demonstrate high economicality and green environmental protection.
Smart Images

Figure CN119480465A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of preparation of high specific capacitance carbon-based materials, and in particular to a two-stage activation preparation method of high specific capacitance supercapacitor carbon-based materials. Background Art
[0002] In recent years, the power battery technology for new energy vehicles has developed very rapidly; supercapacitors are considered to be the mainstream of the next generation of power batteries because of their advantages such as fast charging and discharging speeds, long cycle life and high power density.
[0003] The specific capacitance of electrode materials is a key electrochemical performance parameter of supercapacitors. Self-nitrogen doping and activated nitrogen doping can both improve the specific capacitance of electrode materials. However, few existing methods use peanut straw with a high nitrogen content as a material to prepare high specific capacitance supercapacitor carbon-based materials. In addition, existing preparation methods mostly use single-step chemical activation or physical-chemical two-stage activation to prepare carbon-based materials. The electrochemical properties of the carbon-based materials prepared in this way cannot meet the performance requirements of supercapacitor electrode materials. Summary of the invention
[0004] Based on this, it is necessary to provide a two-stage activation preparation method for a high specific capacitance supercapacitor carbon-based material, the method comprising:
[0005] S1: The discarded peanut straw is washed, dried, crushed and sieved;
[0006] S2: Mix the treated peanut straw and the first activator and place them in a crucible, the mass ratio of the treated peanut straw to the first activator being 1:2, place them in a muffle furnace, and introduce inert gas, heat them to 350-400° C. under the protection of the inert gas, activate them for 60-90 minutes, and cool them to room temperature to obtain an activated initial sample;
[0007] S3: After acid washing, heating and stirring, and standing, the activated initial sample is washed with ultrapure water until the filtrate is neutral, and then filtered and dried to obtain an activated carbon initial sample;
[0008] S4: Mixing the activated carbon initial sample with the second activating agent and placing it in a slide-type microwave reaction pyrolysis furnace, the mass ratio of the activated carbon initial sample to the second activating agent is 1:4, and introducing inert gas, heating to 700° C. under the protection of the inert gas, activating for 10 to 15 minutes, and cooling to room temperature to obtain the activated final sample;
[0009] S5: After the activated sample is acid-washed, heated and stirred, and allowed to stand, it is washed with ultrapure water until the filtrate is neutral, and then filtered and dried to obtain a peanut straw-based carbon-based material.
[0010] Preferably, the mesh size of the sieve is 200-300.
[0011] Preferably, the first activator is a mixture of KCL and NaOH, and KCL:NaOH=1:1.
[0012] Preferably, in S2, the mixing method of the treated peanut straw and the first activator includes:
[0013] The treated peanut straw and the first activator are placed in a planetary ball mill according to a mass ratio, and are subjected to rotary grinding and mixing. The rotation speed of the planetary ball mill is 300 r / min, and the mixing time is 10 to 15 minutes.
[0014] Preferably, the heating rate in S2 under the protection of inert gas is 8° C. / min.
[0015] Preferably, the second activator is a mixture of KCL, K2CO3 and KOH, and KCL:K2CO3:KOH=1:1:2.
[0016] Preferably, in S4, the mixing method of the activated carbon initial sample and the second activating agent includes:
[0017] dissolving the second activator in a mass ratio in a liquid phase to obtain a solution;
[0018] The activated carbon sample is uniformly dispersed in the solution, the solution containing the activated carbon sample is placed in a centrifuge for centrifugal rotation at a speed of 500 r / min, ultrasonically impregnated for 5 minutes, and impregnated for 20 minutes, and the impregnated solution is placed in a watch glass for air drying to obtain a dry solid;
[0019] The dried solid is placed in a planetary ball mill for rotational grinding and mixing. The rotation speed of the planetary ball mill is 300 r / min and the mixing time is 10 to 15 min.
[0020] Preferably, the liquid phase is a uniform solution formed by ultrapure water and anhydrous ethanol, and the ratio of ultrapure water to anhydrous ethanol is 2:1.
[0021] Preferably, the microwave frequency of the slide-rail type microwave reaction pyrolysis furnace is 2.45 GHz, and the microwave power of the slide-rail type microwave reaction pyrolysis furnace is 500 W.
[0022] Preferably, the cooling method in S4 includes:
[0023] After the reaction in the slide-type microwave pyrolysis furnace is completed, the reaction vessel is quickly moved out of the heating zone, and the water cooling system and the air cooling system are turned on to cool down.
[0024] Beneficial effects: This method uses peanut straw as a precursor, adopts a two-stage chemical activation preparation method, and strictly isolates oxygen to prepare a carbon-based material with high specific capacitance. Its electrochemical performance is better than that of existing activated carbon for supercapacitors, and meets the performance requirements of supercapacitor electrode materials. In addition, the use of agricultural waste such as peanut straw to prepare high-performance supercapacitor carbon-based materials has shown the characteristics of high economy and green environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 This is a flow chart of the two-stage activation preparation method in the examples of this application.
[0027] Figure 2 This is a comparison chart of the CV curves of the peanut straw-based carbon-based material prepared in the examples of this application at different scanning rates.
[0028] Figure 3 This is a comparison chart of the GCD curves of the peanut straw-based carbon-based material prepared in the examples of this application at different current densities.
[0029] Figure 4 This is a cyclic stability curve of the peanut straw-based carbon-based material prepared in the examples of the present application at a current density of 10 A / g.
[0030] Figure 5 This is a comparison chart of the CV curves of the peanut straw-based carbon-based material prepared in the examples of the present application and the carbon-based material prepared by other comparative methods at a scan rate of 0.01 V / s.
[0031] Figure 6 This is a comparison chart of the GCD curves of the peanut straw-based carbon-based material prepared in the examples of the present application and the carbon-based material prepared by other comparative methods at a current density of 0.5 A / g.
[0032] Figure 7 This is a comparison chart of the EIS curves of the peanut straw-based carbon-based material prepared in the examples of the present application and the carbon-based material prepared by other comparative methods. DETAILED DESCRIPTION
[0033] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0034] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0035] like Figure 1 As shown, this embodiment provides a two-stage activation preparation method for a high specific capacitance supercapacitor carbon-based material, the method comprising:
[0036] S1: The discarded peanut straw is cleaned, dried, crushed and sieved.
[0037] In this embodiment, the mesh size of the sieve is 200-300.
[0038] The preparation method provided in this embodiment uses agricultural waste such as peanut straw to prepare high-performance supercapacitor carbon-based materials, showing the characteristics of high economy and green environmental protection.
[0039] S2: Mix the treated peanut straw with the first activator and place them in a crucible, the mass ratio of the treated peanut straw to the first activator being 1:2, put them in a muffle furnace, and introduce inert gas. Under the protection of the inert gas, heat to 350-400°C, activate for 60-90 minutes, and cool to room temperature to obtain an activated initial sample.
[0040] In this embodiment, the first activating agent is a mixture of KCL and NaOH, and KCL:NaOH=1:1.
[0041] Furthermore, the mixing method of the treated peanut straw and the first activator includes:
[0042] The treated peanut straw and the first activator are placed in a planetary ball mill according to a mass ratio, and are subjected to rotary grinding and mixing. The rotation speed of the planetary ball mill is 300 r / min, and the mixing time is 10 to 15 minutes.
[0043] In this embodiment, the heating rate in the muffle furnace under the protection of inert gas is 8° C. / min.
[0044] The purpose of the first stage activation is to activate the pore-opening ability of the raw materials and to convert the organic matter in the raw materials into a carbon-based material with a porous structure. This process is crucial to improving the conductivity of activated carbon.
[0045] S3: After acid washing, heating and stirring, and standing, the activated initial sample is washed with ultrapure water until the filtrate is neutral, and then filtered and dried to obtain the activated carbon initial sample.
[0046] S4: After mixing the initial activated carbon sample with the second activating agent, place the mixture in a slide-type microwave reaction pyrolysis furnace, wherein the mass ratio of the initial activated carbon sample to the second activating agent is 1:4, and introduce an inert gas. Under the protection of the inert gas, heat the mixture to 700°C, activate the mixture for 10 to 15 minutes, and cool the mixture to room temperature to obtain a final activated sample.
[0047] In this embodiment, the second activating agent is a mixture of KCL, K2CO3 and KOH, and KCL:K2CO3:KOH=1:1:2.
[0048] Further, the mixing method of the activated carbon primary sample and the second activating agent includes:
[0049] dissolving the second activator in a mass ratio in a liquid phase to obtain a solution;
[0050] The activated carbon sample is uniformly dispersed in the solution, the solution containing the activated carbon sample is placed in a centrifuge for centrifugal rotation at a speed of 500 r / min, ultrasonically impregnated for 5 minutes, and impregnated for 20 minutes, and the impregnated solution is placed in a watch glass for air drying to obtain a dry solid;
[0051] The dried solid is placed in a planetary ball mill for rotational grinding and mixing. The rotation speed of the planetary ball mill is 300 r / min and the mixing time is 10 to 15 min.
[0052] Furthermore, the liquid phase is a uniform solution formed by ultrapure water and anhydrous ethanol, and the ratio of ultrapure water to anhydrous ethanol is 2:1.
[0053] In this embodiment, the microwave frequency of the sliding rail type microwave reaction pyrolysis furnace is 2.45 GHz, and the microwave power of the sliding rail type microwave reaction pyrolysis furnace is 500 W. After the reaction of the sliding rail type microwave reaction pyrolysis furnace is completed, the reaction container is quickly removed from the heating zone, and the water cooling system and the air cooling system are turned on to cool down the temperature, and quickly drop to room temperature.
[0054] S5: After the activated sample is acid-washed, heated and stirred, and allowed to stand, it is washed with ultrapure water until the filtrate is neutral, and then filtered and dried to obtain a peanut straw-based carbon-based material.
[0055] Compared with the prior art, the preparation method provided in this embodiment has the following advantages:
[0056] 1. Different material mixing methods; in S4 of the present embodiment, the material mixing method adopts centrifugal mixing + ultrasonic impregnation + mechanical mixing; first, the second activator is dissolved in the liquid phase, which can not only ensure the good solubility of the second activator, but also regulate the volatilization rate and distribution uniformity of the solution, wherein anhydrous ethanol can reduce the surface tension of the solution, accelerate the volatilization of the solution, and shorten the drying time in the subsequent drying process; under the action of centrifugal force, the agglomeration of activated carbon particles can be reduced, which is conducive to the uniform action of the subsequent second activator; secondly, ultrasonic vibration can further disperse the particles, prevent particle agglomeration, and ensure that the activator can enter the void structure of the activated carbon more evenly; finally, the planetary ball mill can further evenly disperse the second activator and the activated carbon initial sample particles through high-energy rotation grinding, ensure uniform particle size, and more sufficient contact between the second activator and the carbon particles. At the same time, the ball milling process can also increase the surface energy of the particles, which is conducive to improving the reaction activity of the subsequent activation reaction.
[0057] 2. Different activators: In S4 of this embodiment, the second activator is salt + salt + strong base, where the role of KCL is to help control the pore size. Especially when used in combination with KOH, it can regulate the reaction environment during the activation process. K2CO3 and KOH are mixed at high temperature to generate more active potassium oxide. At the same time, the generated CO2 wraps the entire sample environment, avoiding excessive sintering caused by oxygen.
[0058] 3. The two-stage activation methods are different. The first stage uses conventional temperature rise activation, which has a certain promoting effect on the pore-forming ability of activated carbon and provides a highly plastic carbon base for the subsequent second-stage microwave activation. The second stage uses microwave temperature rise activation, which avoids the uneven heating phenomenon in conventional temperature rise activation (to avoid large-scale pore collapse and blockage), and can more actively form a favorable pore structure, improve the electrochemical properties of the material, and ensure the integrity of the material performance, which is crucial for the preparation of supercapacitor materials.
[0059] 4. Since traditional cooling takes a long time, which is equivalent to extending the high temperature time, increasing the activation time, and causing the activated carbon pores to collapse, this embodiment uses a slide rail type microwave reaction pyrolysis furnace. After the reaction is completed, the reaction vessel is quickly removed from the heating zone, and the water cooling system and the air cooling system are turned on to cool down, which can quickly drop to room temperature. This can avoid over-activation and ensure the integrity and excellence of material performance.
[0060] In order to demonstrate the advantages of the peanut straw-based carbon-based material prepared in this embodiment, three other different preparation methods are used to conduct comparative experiments with the preparation method of this embodiment.
[0061] Specifically, the experimental preparation is described as follows:
[0062] In the first comparative method, only the second activator in the preparation method of this embodiment is replaced by a mixture of KCL and KOH in a ratio of 1:1, and the mass ratio of the initial activated carbon sample to the activator is adjusted to 1:2, and the rest of the process remains unchanged.
[0063] The second comparative method only replaces the second activator in the preparation method of this embodiment with a mixture of KCL and KOH in a ratio of 1:2, and adjusts the mass ratio of the initial activated carbon sample to the activator to 1:3, while the rest of the process remains unchanged.
[0064] The third comparative method only replaces the second activator in the preparation method of this embodiment with a mixture of KCL and KOH in a ratio of 1:3, and adjusts the mass ratio of the initial activated carbon sample to the activator to 1:3, while the rest of the process remains unchanged.
[0065] For the convenience of the experiment, the peanut straw-based carbon-based material prepared in this embodiment and the carbon-based materials prepared by the above three comparative methods were respectively manufactured into different three-electrode test materials; the manufacturing process includes:
[0066] Peanut straw-based carbon-based materials / other three carbon-based materials are used as active materials, uniformly stirred and mixed with a certain concentration of PTFE, carbon black, and ethanol in a specific proportion, and placed in a vacuum drying oven at a temperature of 80°C for drying for 1 hour; an appropriate amount of ethanol is added to the dried mixture, stirred and mixed, and continuously squeezed and folded with a small spoon to form a square sticky block, which is wrapped with weighing paper and flattened with an iron rod. Then, 1 / 4 of the square material is cut out and placed in a vacuum drying oven at a temperature of 80°C for drying for 3 hours; after drying, the square material is wrapped with a suitable size of foam nickel and pressed with a tablet press at a pressure of 15 MPa and a pressing time of 1 min to obtain a three-electrode test material.
[0067] The experimental environment is as follows:
[0068] The four different three-electrode test materials manufactured above were tested using the CHI760E electrochemical workstation. Cyclic voltammetry (CV) tests were performed in 6M KOH aqueous electrolyte at a scan rate of 5-200 mV / s. Constant current charge-discharge (GCD) tests were performed at a current density of 0.5-10 A / g and a voltage interval of -1-0 V. Electrochemical impedance spectroscopy (EIS) tests were performed at a frequency of 10 -2 ~10 5Hz. The mass specific capacitance is calculated according to the GCD curve using the formula: C = I·Δt / (ΔU·m), where C is the mass specific capacitance (unit F / g), I is the constant current (unit A), Δt is the discharge time (unit s), m is the mass of the electrode material (unit g), and ΔU is the specified potential change (unit V).
[0069] The experimental results are as follows Figure 2-7 As shown, the analysis is described as follows:
[0070] Figure 2 This is a comparison chart of the CV curves of the peanut straw-based carbon-based material prepared in the examples of the present application at different scan rates. It can be seen that when the scan rate is relatively small, the shape of the CV curve is similar to a rectangle, which is a typical capacitive behavior, indicating that it is mainly double-layer capacitance.
[0071] Figure 3 This is a comparison chart of the GCD curves of the peanut straw-based carbon-based material prepared in the examples of the present application at different current densities. It can be seen that when the current density increases, the curve presents an approximately symmetrical isosceles triangle, which indicates that it has typical double-layer capacitance characteristics and a fast Faraday redox reaction, showing highly reversible charge and discharge behavior.
[0072] Figure 4 This is a cyclic stability curve of the peanut straw-based carbon-based material prepared in the embodiment of the present application at a current density of 10 A / g. It can be seen that after the peanut straw-based carbon-based material prepared in this embodiment is cycled 8000 times at a current density of 10 A / g, the capacitance retention rate is 92.32%, and the cyclic stability is relatively good.
[0073] Figure 5 This is a comparison diagram of the CV curves of the peanut straw-based carbon-based material prepared in the embodiment of the present application and the carbon-based material prepared by other comparative methods at a scan rate of 0.01 V / s. Figure 5 The PC-01 curve is the CV curve of the peanut straw-based carbon-based material prepared in this embodiment, the PC-02 curve is the CV curve of the carbon-based material prepared by the first comparative method, the PC-03 curve is the CV curve of the carbon-based material prepared by the second comparative method, and the PC-04 curve is the CV curve of the carbon-based material prepared by the third comparative method; Figure 5 It can be seen that the CV curve of the peanut straw-based carbon-based material prepared in this embodiment deviates most from a rectangle, indicating that it deviates more from the double-layer capacitance, but the integral area of the curve is the largest, indicating that its specific capacitance is higher.
[0074] Figure 6 This is a comparison diagram of the GCD curves of the peanut straw-based carbon-based material prepared in the embodiment of the present application and the carbon-based material prepared by other comparative methods at a current density of 0.5 A / g. Figure 6The PC-01 curve is the GCD curve of the peanut straw-based carbon-based material prepared in this embodiment, the PC-02 curve is the GCD curve of the carbon-based material prepared by the first comparative method, the PC-03 curve is the GCD curve of the carbon-based material prepared by the second comparative method, and the PC-04 curve is the GCD curve of the carbon-based material prepared by the third comparative method. It can be seen from the GCD curve that the curve presents an approximately symmetrical isosceles triangle, which indicates that it has typical double-layer capacitance characteristics and a fast Faraday redox reaction, showing a highly reversible charge and discharge behavior; Figure 6 It can be seen that the specific capacitances of the four carbon-based materials are 445.0F / g, 361.5F / g, 312.5F / g, and 298.0F / g, respectively. This indicates that the peanut straw-based carbon-based material prepared in this embodiment has the highest specific capacitance. This is due to the fact that K2CO3 reacts with KOH during the activation process to generate more active potassium oxide. At the same time, the generated CO2 wraps the entire sample environment, avoiding excessive sintering caused by oxygen and retaining a better pore structure.
[0075] Figure 7 This is a comparison chart of the EIS curves of the peanut straw-based carbon-based material prepared in the embodiment of the present application and the carbon-based material prepared by other comparative methods, Figure 7 In the figure, the horizontal axis Z' represents the real part of the electrochemical impedance, the vertical axis Z" represents the imaginary part of the electrochemical impedance, the PC-01 curve is the EIS curve of the peanut straw-based carbon-based material prepared in this embodiment, the PC-02 curve is the EIS curve of the carbon-based material prepared by the first comparative method, the PC-03 curve is the EIS curve of the carbon-based material prepared by the second comparative method, and the PC-04 curve is the EIS curve of the carbon-based material prepared by the third comparative method. It can be seen from the EIS curve that the low-frequency region is a slant line, which shows the pseudocapacitive behavior; Figure 7 It can be seen that the charge transfer resistance (Rct) of the four carbon-based materials are 0.180Ω, 1.252Ω, 0.708Ω, and 0.226Ω, respectively, which indicates that the peanut straw-based carbon-based material prepared in this embodiment has a well-developed pore structure and the fastest charge transfer rate.
[0076] Experiments have shown that the carbon-based material prepared in this embodiment has the best performance as a supercapacitor electrode material, with a maximum specific capacitance of 445F / g. At the same time, its cycle stability is relatively ideal, which also shows that the self-nitrogen doping method has a role in improving the electrochemical performance.
[0077] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0078] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.
Claims
1. A two-stage activation preparation method for a high specific capacitance supercapacitor carbon-based material, characterized in that: include: S1: The discarded peanut straw is washed, dried, crushed and sieved; S2: Mix the treated peanut straw and the first activator and place them in a crucible, the mass ratio of the treated peanut straw to the first activator being 1:2, place them in a muffle furnace, and introduce inert gas, heat them to 350-400° C. under the protection of the inert gas, activate them for 60-90 minutes, and cool them to room temperature to obtain an activated initial sample; S3: After acid washing, heating and stirring, and standing, the activated initial sample is washed with ultrapure water until the filtrate is neutral, and then filtered and dried to obtain an activated carbon initial sample; S4: Mixing the activated carbon initial sample with the second activating agent and placing it in a slide-type microwave reaction pyrolysis furnace, the mass ratio of the activated carbon initial sample to the second activating agent is 1:4, and introducing inert gas, heating to 700° C. under the protection of the inert gas, activating for 10 to 15 minutes, and cooling to room temperature to obtain the activated final sample; S5: After the activated sample is acid-washed, heated and stirred, and allowed to stand, it is washed with ultrapure water until the filtrate is neutral, and then filtered and dried to obtain a peanut straw-based carbon-based material.
2. The two-stage activation preparation method of high specific capacitance supercapacitor carbon-based material according to claim 1, characterized in that: The mesh size for sieving is 200-300.
3. The two-stage activation preparation method of high specific capacitance supercapacitor carbon-based material according to claim 1, characterized in that: The first activating agent is a mixture of KCL and NaOH, and KCL:NaOH=1:
1.
4. The two-stage activation preparation method of high specific capacitance supercapacitor carbon-based material according to claim 1, characterized in that: In S2, the mixing method of the treated peanut straw and the first activator includes: The treated peanut straw and the first activator are placed in a planetary ball mill according to a mass ratio, and are subjected to rotary grinding and mixing. The rotation speed of the planetary ball mill is 300 r / min, and the mixing time is 10 to 15 minutes.
5. The two-stage activation preparation method of high specific capacitance supercapacitor carbon-based material according to claim 1, characterized in that: The heating rate in S2 under the protection of inert gas is 8°C / min.
6. The two-stage activation preparation method of high specific capacitance supercapacitor carbon-based material according to claim 1, characterized in that: The second activating agent is a mixture of KCL, K2CO3 and KOH, and KCL:K2CO3:KOH=1:1:
2.
7. The two-stage activation preparation method of high specific capacitance supercapacitor carbon-based material according to claim 1, characterized in that: In S4, the mixing method of the activated carbon initial sample and the second activating agent includes: dissolving the second activator in a mass ratio in a liquid phase to obtain a solution; The activated carbon sample is uniformly dispersed in the solution, the solution containing the activated carbon sample is placed in a centrifuge for centrifugal rotation at a speed of 500 r / min, ultrasonically impregnated for 5 minutes, and impregnated for 20 minutes, and the impregnated solution is placed in a watch glass for air drying to obtain a dry solid; The dried solid is placed in a planetary ball mill for rotational grinding and mixing. The rotation speed of the planetary ball mill is 300 r / min and the mixing time is 10 to 15 min.
8. The two-stage activation preparation method of high specific capacitance supercapacitor carbon-based material according to claim 7, characterized in that: The liquid phase is a uniform solution formed by ultrapure water and anhydrous ethanol, and the ratio of ultrapure water to anhydrous ethanol is 2:
1.
9. The two-stage activation preparation method of high specific capacitance supercapacitor carbon-based material according to claim 1, characterized in that: The microwave frequency of the slide-rail type microwave reaction pyrolysis furnace is 2.45 GHz, and the microwave power of the slide-rail type microwave reaction pyrolysis furnace is 500W.
10. The two-stage activation preparation method of high specific capacitance supercapacitor carbon-based material according to claim 1, characterized in that: Cooling methods in S4 include: After the reaction in the slide-type microwave pyrolysis furnace is completed, the reaction vessel is quickly moved out of the heating zone, and the water cooling system and the air cooling system are turned on to cool down.
Citation Information
Patent Citations
Two-step activation preparation method of activated carbon and application thereof in supercapacitor
CN106145110A
Garlic-husk-base active carbon electrode material for super-capacitor, and preparation method of the same
CN107039193A
Preparation method of straw-based activated carbon supercapacitor electrode material with energy storage efficiency enhanced by acidic mine wastewater
CN110240161A
Preparation method of novel coal-based porous carbon electrode material
CN114890420A
Preparation method and application of biomass activated carbon-based electrode material
CN115744900A